Molecular interactions mediated by the surface antigen CD5 during T lymphocyte activation - Broszeit, Richard (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.M.S. (Medical Biochemistry)) -- University of Stellenbosch, 1996.